The Integration of Timber Enterprises of the Khanty-Mansiysk Autonomous Okrug - Yugra - Kislukhina, Irina Anatolyevna (Economy of Regions, 2018)
The article investigates the timber enterprises’ integration in Khanty-Mansiysk Autonomous Okrug - Yugra as a way to improve the efficiency of the timber industry. Currently, in the region, only 10 of 130 timber enterprises are large and mediumsized enterprises. The other companies are small and chronically underfunded. These small enterprises use outdated equipment and production technology, are unable to organize wood processing and reforestation; to develop forest infrastructure. However, the integration of timber industry enterprises can become the way to address this situation. The article discusses various types of possible enterprises’ integration, such as vertical and horizontal integrations, the combined and unrelated diversification (financial integration). The combined diversification is a mixed type of the integration of enterprises from related and unrelated industries. This type of integration is most in keeping with the characteristics of the development of timber industry of Khanty-Mansiysk Autonomous Okrug - Yugra. The combined diversification will maximize the effect from the association of enterprises. The author has justified the rationale for establishing six integrated industrial and financial associations (UFA) according to improved forest and economical zoning of Okrug area. I defined the profile of each IIFA taking into account of special aspects of forest resources as well as social and economical development characteristics of the area and demand for the products. In Khanty-Mansiysk Autonomous Okrug - Yugra, the integrated industrial and financial associations will address four critical challenges of the socio-economic development of the region. Firstly, these associations will contribute to the diversification of the economy. Secondly, they will enable the production of new types of forest products. Thirdly, the creation of the integrated industrial and financial associations will increase the efficiency in use of wood raw materials (including low-grade wood and wood waste). And last, it will enhance job creation and wage increases for the employees in the forest industry. The integration in the timber industry of Khanty-Mansiysk Autonomous Okrug can be applied by other regions of Russia. However, technologies of integration have to be adapted to socio-economic and forest vegetation conditions of a certain region.